Contemporary Fiqh al-Mu'amalat and Legal Reform in Indonesia's Sharia Economic System - Edi Mulyono; Anita Niffilayani; Is Susanto; Jalaludin Ar-Rumei (Journal of Nusantara Economy, 2026)
The rapid development of the sharia economy in Indonesia has encouraged the emergence of various contemporary financial transactions that require adaptive legal responses. Classical fiqh al-mu'amalat, while providing fundamental principles for economic activities, often faces challenges in addressing modern financial instruments such as Islamic banking, financial technology, digital transactions, and Islamic capital markets. This study aims to analyze the role of contemporary fiqh al-mu'amalat in the process of legal reform within Indonesia's sharia economic system. Employing a normative juridical approach and qualitative library research methods, this study examines legislation, fatwas of the National Sharia Council-Indonesian Ulema Council (DSN-MUI), and scholarly literature on Islamic economic law. The findings indicate that legal reform in Indonesia's sharia economy has been significantly influenced by contemporary ijtihad and maqasid al-shariah approaches, resulting in more contextual and adaptive regulations. The integration of classical fiqh principles with modern legal needs has contributed to the development of an inclusive and dynamic sharia economic system. This study concludes that contemporary fiqh al-mu'amalat serves as a fundamental basis for legal reform and strengthens the institutional framework of Indonesia's sharia economy